2014
DOI: 10.1016/j.cej.2014.02.051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of accelerated carbonation on AOD stainless steel slag for its valorisation as a CO2-sequestering construction material

Abstract: Effect of accelerated carbonation on AOD stainless steel slag for its valorisation as a CO 2-sequestering construction material,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(51 citation statements)
references
References 42 publications
0
51
0
Order By: Relevance
“…The CO 2 uptake was 10-15 %. Salman et al [37] made similar compacts of AOD slag that reached compressive strengths of 34 MPa after 3 weeks in a carbonation chamber at atmospheric pressure with 5% CO 2 , and 59.8 MPa after 15 hours in a carbonation reactor at 8 bar CO 2 and 80°C.…”
Section: Case 2: Carbonate Bonded Compactsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CO 2 uptake was 10-15 %. Salman et al [37] made similar compacts of AOD slag that reached compressive strengths of 34 MPa after 3 weeks in a carbonation chamber at atmospheric pressure with 5% CO 2 , and 59.8 MPa after 15 hours in a carbonation reactor at 8 bar CO 2 and 80°C.…”
Section: Case 2: Carbonate Bonded Compactsmentioning
confidence: 99%
“…Far fewer research has been carried out with the purpose of using accelerated carbonation to make construction materials [17,[35][36][37]. Tables 1 and 2 summarize reports in the scientific literature on accelerated carbonation as a means to produce carbonate bonded blocks (Table 1) and aggregates (Table 2) from alkaline residues.…”
Section: Precursors and Comentioning
confidence: 99%
“…It has been observed that the carbonated SS can potentially be used as partial cement replacement materials (Liang et al, 2012;Salman et al, 2014). However, in order to make exsitu carbonation more economically feasible, a breakthrough on the use of carbonated solid wastes or products should be sought in the areas of technology, regulation, institution and finance.…”
Section: Cost Evaluation and Energy Consumptionmentioning
confidence: 99%
“…The wastewater generated in the same industries also can be introduced for the carbonation process to avoid the use of freshwater resources. After carbonation, the slurry is separated into (Teir et al, 2007;Reddy et al, 2010;Sanna et al, 2012a;Abo-El-Enein et al, 2013;Dri et al, 2013;Hekal et al, 2013;Muriithi et al, 2013;Santos et al, 2013b, c;Dri et al, 2014;Jo et al, 2014;Reynolds et al, 2014;Salman et al, 2014;Santos et al, 2014;Ukwattage et al, 2014). carbonated solid wastes and liquid solution.…”
Section: Types Of Carbonation Processesmentioning
confidence: 99%
“…Several studies have been carried out to evaluate the effect of carbonation curing on the properties of blended cement and/or (Teir et al, 2007;Reddy et al, 2010;Sanna et al, 2012;Abo-El-Enein et al, 2013;Dri et al, 2013;Hekal et al, 2013;Muriithi et al, 2013;Santos et al, 2013a;Dri et al, 2014;Jo et al, 2014;Reynolds et al, 2014;Salman et al, 2014;Santos et al, 2014;Fujii et al, 2015;Ukwattage et al, 2015). concrete masonry (El-Hassan and Shao, 2015).…”
Section: Integrated Alkaline Wastes Treatment With Co 2 Fixation and mentioning
confidence: 99%